2010
DOI: 10.1111/j.1740-8261.2010.01762.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Magnetic Resonance Safety of Veterinary Radiofrequency Identification Devices at 1 t

Abstract: Implants containing metallic components have the potential to become heated or move within the patient while in the magnetic resonance (MR) environment. Despite containing a ferromagnetic core and having been in use for over 20 years, no information is available on the safety of veterinary radiofrequency identification devices during MR examinations. These devices are the most commonly encountered metallic implants in dogs and cats undergoing MR imaging. Three commercial veterinary microchips were evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
5
0
4
Order By: Relevance
“…We found that the functionalities of card tags remain unchanged after exposure to MRI examination. Although functional alteration of active 2.4 GHz RFID tags was not reported under 1.5 T MRI scanners, we need such investigation for lower field systems because of the complexities involved in the design of MRI scanners [24]. We found severe artifacts in the captured MRI when the region of interest (ROI) was closer to the RFID tags.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We found that the functionalities of card tags remain unchanged after exposure to MRI examination. Although functional alteration of active 2.4 GHz RFID tags was not reported under 1.5 T MRI scanners, we need such investigation for lower field systems because of the complexities involved in the design of MRI scanners [24]. We found severe artifacts in the captured MRI when the region of interest (ROI) was closer to the RFID tags.…”
Section: Discussionmentioning
confidence: 95%
“…To the best of the author's knowledge, only one study [21] has discussed the usage of active 2.4 GHz RFID tags (card tags) in an MRI environment of 1.5 T, and concluded that tested tags were safe with no change in their functionality and induced severe artifacts in captured MRI images if the area of imaging is closer to tags. Since these results cannot be generalized to other MRI scanners with different field strengths, because of the difference in the design of MRI scanners by various manufacturers and complexity involved in the EM field interactions [24]. Thus, we decided to conduct similar tests with low field 0.3 T MRI scan using more number of sequences and different types of tags.…”
Section: Introductionmentioning
confidence: 99%
“…It can be assumed that scanners of field strength between these extremes should similarly not damage the information stored on the transponder. Results from recent studies, analyzing the function of different types of implanted microchips with 1.0 and 1.5 Tesla systems have also shown that all microchips can be read out correctly after the application of routine scan protocols , …”
Section: Discussionmentioning
confidence: 99%
“…There are several ways in which the MRI scanner and the microtransponder might interact: for example, the magnetic forces or the radio waves involved in each technology may interfere with one another. Deterioration of image quality due to susceptibility of artifacts, movement of microchips, and the heating of the transponder is documented . The technical components of the transponder could be damaged by heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation